RELATIONSHIP OF VOLT-AMPERE CHARACTERISTICS OF SOLAR ELEMENTS TO TEMPERATURE (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
Today's in the day people to energy has been desire from day to day increased is going of this main reasons to all of us known has been the world of the population sharp respectively increased to go , work release and of industry development of energy each in the field is necessary. Including Energy in Uzbekistan has been need increased is going in our country to energy has been desire full satisfy in order to be ecological clean energy from sources use programs work coming out. Also alternative from energy the sun from energy to use to the road to put the economy development and again recoverable from resources reasonable to use take will come in this regard take going one series affairs own the effect is showing. Especially in our country the sun from energy use possibilities size with another from countries separate stands [1-5].